Efficacy and safety of oral SOCG in treatment of major depressive disorder: A protocol for a phase II, randomized, double-blind, placebo controlled, parallel-groups, dose finding exploratory study. Issue 35 (August 2019) - Kim, Ju Yeon; Seo, Young Kyung; Lee, Ji-Yoon; Kang, Weechang; Chee, Ik-Seung; Choi, Kwang-Yeon; Jung, In Chul
Abstract: Introduction: Major depressive disorder (MDD) is a common condition worldwide, and leads to degradation in quality of life and large socioeconomic costs. There has been increasing demand for new therapies with fewer side effects. SOCG (SOCG tablet) is a modified prescription of So-ochim-tang, which is widely used in Traditional Korean Medicine to treat MDD. We aim to evaluate the efficacy of SOCG in treating MDD, and identify the optimum dose. Design: The protocol we are following is that of a Phase II clinical trial with a randomized, double blinded, placebo controlled, and parallel design. One hundred forty-eight participants will be randomly divided into 4 groups and treated for 8 weeks. Outcome measures: The primary outcome will be the score in the Korean Version of the Hamilton Depression Rating Scale. Scores in the Korean version of the Beck Depression Inventory-II Korean Symptom Check List-95 (KSCL-95), State Trait Anxiety Inventory-Korean version, State- Trait Anger Expression Inventory- Korean version (STAXI-K), Insomnia Severity Index (ISI), and the EuroQol-5 Dimension (EQ-5D) will be considered as secondary outcomes. Discussion and Conclusions: Demonstration of human safety and efficacy of SOCG in the present trial and identification of the appropriate dose will justify a New Drug Application and a phase III clinical trial. Further, we expect that this new antidepressant will be able to increase cure rates, and alleviate the burden of medical expenses. Trial registration number: Clinical Research Information Service, Republic of Korea (KCT0002763).